Speech stuttering assessment using sample entropy and Least Square Support Vector Machine - Muthusamy, Hariharan, Dr.; Vijean, Vikneswaran; Chong, Yen Fook; Sazali, Yaacob, Prof. Dr. (Institute of Electrical and Electronics Engineers (IEEE), 2013)
Link to publisher's homepage at http://ieeexplore.ieee.org/